Analysis of lymph node spread and its prognostic significance in ampullary adenocarcinoma: A retrospective study - Zhang, Zheng-Yun; Guan, Jiao; Wang, Xin-Ping; Hao, Di-Si; Zhou, Zun-Qiang (Frontiers in Surgery, 2022)
Background: Nodal status is a vital prognostic factor for ampullary adeneocarcinoma. This study was designed to evaluate the clinical significance of the positive nodes in this disease. Methods: Data from 110 patients undergoing curative pancreatoduodenectomy for ampullary adenocarcinoma between January 2007 and December 2018 were retrospectively collected and analyzed. Results: The median number of lymph nodes per patient was 32 (20-46). Metastatic lymph nodes were found in 84 (76.4%) patients. In patients with positive nodules, the most commonly involved nodes were the #13 (80.1%) and #17 (78.6%) nodes followed by #12 (69.0%) and #8 nodes (57.1%). Patients with 3-4 positive nodes among #13, #17, #12, #8 had the worst survival rate than patients with 0 or 1-2 nodes. Conclusions: Ampullary adenocarcinoma commonly spreads to #13, #17, #12, #8 lymph nodes. These nodes affected patients’ survival dramatically.